2015
DOI: 10.1007/s00520-015-2627-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing cancer care through mobile health

Abstract: The survival rates for patients living with cancer are increasing, due to recent advances in detection, prevention and treatment. It has been estimated that there were 28 million cancer survivors around the world in 2012. In the UK, for patients diagnosed in 2007, it is predicted that more than half of them will survive their cancer for 5 years or more. A large majority of cancer survivors report unmet supportive care needs and distressing symptoms and adverse long-term consequences related to their cancer. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 72 publications
(44 reference statements)
1
64
0
2
Order By: Relevance
“…Focusing on patient experiences, as oral hygiene researchers including Michie et al have suggested, techniques to foster patient adherence could integrate additional selfmonitoring techniques, e.g., daily diaries, use of new media (e.g., putting reminders and using smartphone apps as assessment tools) or emotional support, e.g., motivational interviews [27,[38][39][40]. Such techniques should be incorporated into standard practice as well as future research.…”
Section: Discussionmentioning
confidence: 96%
“…Focusing on patient experiences, as oral hygiene researchers including Michie et al have suggested, techniques to foster patient adherence could integrate additional selfmonitoring techniques, e.g., daily diaries, use of new media (e.g., putting reminders and using smartphone apps as assessment tools) or emotional support, e.g., motivational interviews [27,[38][39][40]. Such techniques should be incorporated into standard practice as well as future research.…”
Section: Discussionmentioning
confidence: 96%
“…It showed a better continuity of patient care, reduction of travel costs, shorter waiting times, and importantly no reported adverse events. As telemedicine is based on electronic storage, data can be saved long term and more efficiently and with smaller space compared to paper-based documentation [20]. …”
Section: Discussionmentioning
confidence: 99%
“…The optimization of cancer management through eHealth is a reality and regulation to ensure patient safety is taking the first steps. 7 Despite the opportunities provided by eHealth in the field of cancer management, issues concerning the personcenteredness of the services delivered and the adequacy of connection between research and clinical practice are raised. 8,9 The anticipation and possible solution of such issues might be achieved by adopting a methodological approach to development of patient technologies that integrates users' perspectives from early design stages throughout development, evaluation, and implementation.…”
mentioning
confidence: 99%